Analisis Sentimen Opini Publik Tentang Gempa Megathrust di Indonesia Menggunakan Metode Support Vector Machine dan Naïve Bayes - Kurniawan, Dicky; Satria, Muhhammad Najib Dwi (Forum Kerjasama Pendidikan Tinggi, 2024)
Indonesia is a country prone to natural disasters, especially earthquakes. One of the biggest threats is the potential for megathrust earthquakes that can cause severe damage and loss of life, especially in the Jakarta area. In the digital era, information about the potential for megathrust earthquakes is widely disseminated through social media platforms such as YouTube, which then triggers various opinions and comments from the public. A video titled